Near dipole-dipole interaction induced control of high-precision three-dimensional atom localization via probe absorption in a four-level phase-coherent atomic medium - Aniket Banerjee; Pradipta Panchadhyayee; Bibhas Kumar Dutta (Scientific Reports)
Abstract It is newly proposed that the presence of the near dipole-dipole (NDD) interaction effect in an optically dense atomic ensemble may be very useful for controlling high-precision atom localization. In the present work based on observing the NDD effect-induced space-dependent-absorption of a weak probe field operating in a partially closed four-level Y-type atomic system, we have shown the NDD parameter being an efficient control knob along with the other system parameters for easier optimization of the localization pattern with enhanced detection probability in three-dimensional (3D) space. Controlling localization patterns at lower and larger values of NDD parameter is discussed at different physical conditions. In the present model, we mention that the maximum detection probability of the atom is found with the spatial resolution limit having localization volume nearly of the order of $$(λ /100)^3$$ . The efficacy of the present model is in finding its application in atom nanolithography and atom imaging, which are important for quantum information processing and technology.